2014
DOI: 10.1017/s0022215114000206
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of inferior turbinates coblation in children

Abstract: Inferior turbinate reduction by coblation is an effective and safe procedure in children aged six years and older. The positive outcomes seem to be long-lasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…5 Of the prior studies showing a benefit of IT in the pediatric population, most did not control for concurrent airway procedures, making it difficult to assess the efficacy of the turbinate reduction alone. 1,2,[6][7][8][9] A few studies [10][11][12][13] have limited their study population to children undergoing inferior turbinate reduction alone, but these studies have small sample sizes and short followup. The present study aimed to assess the outcomes of pediatric patients undergoing isolated IT.…”
mentioning
confidence: 99%
“…5 Of the prior studies showing a benefit of IT in the pediatric population, most did not control for concurrent airway procedures, making it difficult to assess the efficacy of the turbinate reduction alone. 1,2,[6][7][8][9] A few studies [10][11][12][13] have limited their study population to children undergoing inferior turbinate reduction alone, but these studies have small sample sizes and short followup. The present study aimed to assess the outcomes of pediatric patients undergoing isolated IT.…”
mentioning
confidence: 99%
“…37 Since then, multiple other studies have confirmed long-lasting improvement of nasal symptoms with low rates of postoperative crusting and epistaxis and no reports of synechiae or ozena (Table 2). 13,38,39 Furthermore, there is evidence that preoperative assessment may help differentiate patients who would most benefit from radiofrequency coblation. Yilmaz et al showed that the response to a preoperative topical vasoconstrictor drop test may predict long-term efficacy of RVTR in pediatric patients.…”
Section: Submucous Microdebridementmentioning
confidence: 99%
“…Although not studied extensively, bilateral inferior turbinoplasty has been shown to be an effective, safe procedure in children that can potentially improve nasal congestion 7 and snoring, 8 and it does not significantly increase complication rates when performed concurrently with T/A. 9,10 Tonsillectomy/adenoidectomy with bilateral inferior turbinoplasty (T/A-BITR) has been demonstrated to significantly improve objective sleep parameters and subjective quality-of-life scores compared to T/A alone in the pediatric population. 11 Decision analysis can help further explore the potential success of T/A-BITR compared to the current standard of T/A.…”
mentioning
confidence: 99%